2001
DOI: 10.1212/wnl.57.3.481
|View full text |Cite
|
Sign up to set email alerts
|

A 1-year, placebo-controlled preservation of function survival study of donepezil in AD patients

Abstract: Patients with AD continue to show detectable disease progression over time, but treatment with donepezil for 1 year was associated with a 38% reduction in the risk of functional decline compared with placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
349
1
8

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 466 publications
(372 citation statements)
references
References 22 publications
14
349
1
8
Order By: Relevance
“…Improvement in ADLs (as measured by the Progressive Deterioration Scale 87 ) was seen at 52 weeks but not at earlier time points, and cognitive improvement was observed in a secondary measure (Mini-Mental State Examinationă 88 [MMSE]: scale: 0-30 points; lower scores ϭ impairment). In the study by Mohs et al, 83 which enrolled 431 patients with moderate AD, a higher proportion of patients receiving placebo (56%) compared with those receiving donepezil (41%) met criteria for clinically evident functional decline, although this difference was not significant. In addition, no difference in the mean functional status in patients completing the study was found between the donepezil and placebo groups.…”
Section: Long-term Symptomatic Efficacymentioning
confidence: 95%
See 2 more Smart Citations
“…Improvement in ADLs (as measured by the Progressive Deterioration Scale 87 ) was seen at 52 weeks but not at earlier time points, and cognitive improvement was observed in a secondary measure (Mini-Mental State Examinationă 88 [MMSE]: scale: 0-30 points; lower scores ϭ impairment). In the study by Mohs et al, 83 which enrolled 431 patients with moderate AD, a higher proportion of patients receiving placebo (56%) compared with those receiving donepezil (41%) met criteria for clinically evident functional decline, although this difference was not significant. In addition, no difference in the mean functional status in patients completing the study was found between the donepezil and placebo groups.…”
Section: Long-term Symptomatic Efficacymentioning
confidence: 95%
“…82,83 Doody et al 79 presented results from 763 patients enrolled in a 144-week, open-label extension of 2 preceding RCTs. The deterioration in the mean change from baseline of the Alzheimer's Disease Assessment Scale 84 cognitive subscale (ADAS-Cog: 0-70 points; higher scores ϭ impairment) was 7.4 to 9.1 points for the group that received 5 mg/d and 7.9 to 10.0 points for the group that received 10 mg/d, depending on the study.…”
Section: Long-term Symptomatic Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…However, AChE inhibitors have been less promising therapeutically as they produce only modest improvements in cognitive function (Bryson and Benfield, 1997;Greenberg et al, 2000;Mohs et al, 2001;Winblad et al, 2001) along with undesirable side effects (Wilkinson, 1999;Dunn et al, 2000;Imbimbo, 2001). …”
Section: Introductionmentioning
confidence: 99%
“…One-year clinical trials in patients with mild to moderate AD showed a mean treatment difference of 1.6 points on the MMSE in favor of donepezil. 42,43 In contrast to the preservative effect seen in these clinical trials, Ms. A's cognition was greatly enhanced at the 6-and 12-month assessments of her treatment. Over the course of 1 year, her mean response to treatment was 5 points on the MMSE.…”
Section: Rivastigminementioning
confidence: 84%